(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objectives: To develop and validate a folder on diabetic foot prevention aimed at patients and their families. Method: Methodological study carried out in two stages. The first one was bibliographic review for the construction of the folder through the search of articles and manuals on the diagnosis, problems faced, self-care, prevention and the main interventions of the diabetic foot in the database at the National Library of Medicine. The second stage was related to the validation process, with the participation of 23 stomatherapist nurses. The content validity index (CVI) was used to assess the validity of the folder and Kappa as an indicator of agreement. Results: The technology’s global CVI in the first evaluation showed an overall CVI = 0.91, and an overall Kappa index = 0.81. After reformulating the material based on the judges’ suggestions, a second validation cycle indicated CVI = 0.99 and Kappa CVI = 0.98. Conclusion: The proposed technology was considered validated by specialists in terms of objectives, content, relevance, figures, writing style and content, presenting high scores in the CVI and Kappa index, suggesting that the material can be used to work on the prevention of diabetic foot with the patients and their families.